PENAMPUNGAN LIMBAH DAN PENGARUHNYA TERHADAP LAJU SINTASAN DAN PERTUMBUHAN NILA MERAH DALAM KERAMBA JARING APUNG DI WADUK SERMO, YOGYAKARTA - Rustadi Rustadi (Universitas Gadjah Mada, 2008)
The aim of this research was to find out the effect of waste collection in red tilapia culture using floating net cage to the quantity of the waste and degradation rate, on survival and growth rate of fish. A completely randomized design was performed in the experiment consist of two waste collections; namely: with and without collection, and three fish stocking weights of 2.5 kg, 5 kg and 7.5 kg fish/cage, with two replicates each. Floating net cages with the size of wide, length and height of 1 x 1 x 1.2 m were used in the experiment. To collect fish waste, inverted cone-shape plastic collector was attached to the cage and hanged 15 cm below the cage. Fingerling size ranged from 50 – 70 gram/fish were divided into two groups and stocked in the different replication. The fish were cultured for 84 days and fed daily with commercial feed (25-27% protein content) at the rate of 3% fish body weight. Waste sample were collected and incubated in different temperature of 20, 25 and 30 oC with deviation of 1 oC and 3 replicate each. Parameter of total dissolved solid (TDS), total suspended solid (TSS), DO, BOD, CO2 and NH3 were checked every 5 days for 20 days, and total N and total P were check at the beginning and the end. Data were analyzed statistically using confidence level of 95%. Total waste collected were ranged 0.109-0.117 kg dry weight/cage and waste lossing due to fixing collector 15 cm under the cage was about 14.44%. The addition of waste collection in fish culture tended to make lower survival and growth rate, meanwhile more stocking weight may increase fish harvest. Fish waste decomposed faster in higher temperature, indicate that the waste decomposition could decrease water quality and increase concentration of N and P nutrients.